2010
DOI: 10.1001/archophthalmol.2009.387
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Corticosteroid-Induced Ocular Hypertension in Sheep by Anecortave

Abstract: Objective: To confirm the ocular hypotensive effects of anecortave acetate on an ovine model for steroid-induced ocular hypertension. Eyes of normal sheep exhibit a robust steroid-induced ocular hypertensive response. Recent observations in an uncontrolled, interventional case series indicated that anecortave elicited hypotensive effects when administered as a sub-Tenon depot in the eyes of a small sample of patients with glaucoma. Methods: Intraocular pressure (IOP) was monitored by Perkins applanation tonome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…There are quite a few studies using applanation tonometry in animals (Priehs et al, 1990;Miller et al, 1990;Miller et al, 1991;Dziezyc et al, 1992;Passaglia et al, 2004;Candia et al, 2010;Gerometta et al, 2010;Ribeiro et al, 2010;Rusanen et al, 2010), but we found no reports on the assessment of the mean IOP in healthy sheep using the applanation tonometer Tonopen XL e . The purpose of this study was to determine the mean IOP in healthy adult sheep using applanation tonometry with Tonopen XL e .…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…There are quite a few studies using applanation tonometry in animals (Priehs et al, 1990;Miller et al, 1990;Miller et al, 1991;Dziezyc et al, 1992;Passaglia et al, 2004;Candia et al, 2010;Gerometta et al, 2010;Ribeiro et al, 2010;Rusanen et al, 2010), but we found no reports on the assessment of the mean IOP in healthy sheep using the applanation tonometer Tonopen XL e . The purpose of this study was to determine the mean IOP in healthy adult sheep using applanation tonometry with Tonopen XL e .…”
Section: Introductionmentioning
confidence: 61%
“…The MacKay-Marg applanation tonometer, which is considered the golden standard in Veterinary Medicine, has no longer been manufactured. A portable Mackay-Marg-type tonometer (Tonopen) has been widely used among veterinary ophthalmologists and has been assessed in dogs, cats, horses, and in some extent in sheep (Miller et al, 1990;Priehs et al, 1990;Miller et al, 1991;Dziezyc et al, 1992;Passaglia et al, 2004;Candia et al, 2010;Gerometta et al, 2010;Rusanen et al, 2010); however, a controlled study measuring the baseline IOP in healthy sheep, using applanation tonometry with Tonopen XL e , has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Adenovirally (AdV) mediated MMP1 overexpression lead to a reversal of steroid-induced IOP elevation (Gerometta et al, 2010). Similarly, treatment with anterior juxtascleral administration of anecortave acetate has been shown to prevent IOP elevation in sheep (Candia et al, 2010). The sheep model has also been used to determine that tPA can prevent as well as reverse steroid-induced IOP elevation (Candia et al, 2014; Gerometta et al, 2013).…”
Section: In Vivo-modelsmentioning
confidence: 99%
“…In addition, anecortave depot also reverted elevated IOP to baseline levels in the eyes of normal sheep who received the injection after IOP elevation [72].…”
Section: Anecortave Acetatementioning
confidence: 82%